Características físico-químicas de amidos de genótipos de bananeiras - Mesquita, Camila de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Banana (Musa spp.) is one of the most cultivated fruit in the countries of tropical and subtropical climate. Brazil has featured on the world stage, but the accumulation of losses in the production chain of banana is quite large. One way to reduce these losses is to use banana as a source of starch and special flours. The starch varies in form and function within and among plant species and even in the same cultivar under different growing conditions. This variability provides starches with diverse properties. In this line, this project aimed to compare the pulp of the green fruit from banana genotypes, as well as physico-chemical properties of starches. Five genotypes of banana were planted in the farm San Manuel/UNESP and cultured in systematic design in split plots (ten plants/plot). The clusters with green fruits were harvested in the first cycle of production and managed in the processing lab of CERAT/UNESP to obtain the starches. Fresh fruits were analyzed for moisture, phosphorus and starch. In order to compare the characteristics of starches of banana genotypes without phosphorus fertilization, these were analyzed for crystallinity, size distribution of granules, scanning electron microscopy, chemical composition, phosphorus content, apparent amylose, resistant starch, pasting and thermal properties, swelling power and solubility. The analysis reveals that the fruits of 'Prata-Anã' had a higher amount of dry matter (41.95 %). The greatest content of starch in fruit was observed in 'Maçã'. The content of phosphorus in fruit does not differed statistically. The granules of banana starches were large (36.58 to 47.24 microns), oval, had crystallinity standard type B and index of crystallinity with statistically similar values (31.94 % to 34.06 %). The results also showed that the native starches extracted from green bananas had phosphorus contents ranging from 0,003 % ('Grand Naine') ...

A banana (Musa spp.) é uma das frutas mais cultivadas nos países de clima tropical e subtropical. O Brasil possui destaque no cenário mundial, contudo, o acúmulo de perdas na cadeia produtiva da banana é grande. Uma forma de reduzir essas perdas é utilizando a banana como fonte de amido e farinhas especiais. O amido varia em forma e funcionalidade entre e dentro de espécies botânicas e até mesmo em um mesmo cultivar sob diferentes condições de cultivo. Esta variabilidade fornece amidos com diversas propriedades. Nesta linha, este projeto objetivou comparar a polpa dos frutos verdes entre os genótipos de bananeiras, bem como as características físico-químicas de seus amidos. Cinco genótipos de bananeiras foram plantados na Fazenda Experimental São Manuel/UNESP e cultivados em delineamento sistematizado em parcelas subdivididas (dez plantas/parcela). Os cachos com os frutos verdes foram colhidos no primeiro ciclo de produção e manejados no laboratório de processamento do CERAT/UNESP para a obtenção dos amidos. Os frutos frescos foram analisados quanto aos teores de umidade, fósforo e amido. Visando à comparação das características dos amidos dos genótipos de bananeiras, estes foram analisados quanto à cristalinidade, distribuição de tamanho de grânulos, forma dos grânulos, composição centesimal, teores de fósforo, amilose aparente e amido resistente, propriedades de pasta, propriedades térmicas, poder de inchamento e solubilidade. A análise dos frutos revelou que os frutos verdes de banana 'Prata-Anã' possuem maior quantidade de matéria seca (41,95 %). O maior teor de amido dos frutos é pertencente ao genótipo 'Maçã'. O teor de fósforo do frutos não diferiu estatisticamente. A análise do tamanho dos grânulos de amido dos genótipos de banana evidenciou que estes são grandes (36,58 a 47,24 μm), ovalados, possuem padrão de cristalinidade tipo ...
Physico-chemical properties of starches from different banana genotype
Keywords: Banana - Cultivo; Amido - Análise; Viscosidade; Plantas - Efeito do fosforo; Banana products